The Effect of Cognitive Acceleration Strategy on EFL Intermediate School Students' Achievement - Mahmood, Alaa Adnan; Yahya, Nagham Qadoory (Journal of Tikrit University for Humanities, 2024)
Cognitive Acceleration is an intervention programme with the purpose of accelerating students' ‘natural’ development process through different stages of thinking ability, towards the type of abstract and logical thinking. The current study aims at finding out the effect of Cognitive Acceleration Strategy on EFL intermediate school students' achievement; and finding out whether there is any significant difference between the experimental group in the pre-test and the posttest. To achieve the aims of the study, a "quisi experimental posttest design" is adopted. The sample consists of 82 second grade male students, who have been randomly selected and divided into two equal groups, i.e., experimental and control groups. Both groups are equalized in their ages, parents' educational level, their English scores in the previous year, and their achievement in the pretest. The two groups have been taught the same instructional material for a period of eight weeks. An achievement test has been constructed, validated, its reliability obtained, its items analyzed, and then applied to the two involved groups of students at the end of the instructional period of the current study. The obtained results are as follows: There is a significant difference between the achievement of the two groups, and in favour of the experimental group; and there is a significant difference between the students' achievement in the pretest and that in the posttest, and in favour of latter. Finally, the study ends up with a number of conclusions, recommendations.